La pequeña razón en el océano de lo real: El sendero intermedio de la poesía - Palacios Cruz, Víctor Hugo (Mercurio Peruano, 2013)
Just when we desire most to understand something, our reason offers doubts and silence. Since it is metaphor and poetry –as extreme resources– appear, that is, a way of referring situated between the excessive confidence and dejection. The actual anxiety to get some simple and different ideas inevitably impoverish what it’s really worth to think about, what is better to express by a suggestive way than in an exact and objective form. Just as in an open and provisional expression it is possible to preserve the vitality of philosophizing, it is understood like “love” –a constant search– nor as arrogant and final possession of knowledge. It is as far from rational vanity as it from helplessness agnosticism.